Environmental Enrichment Induces Epigenomic and Genome Organization Changes Relevant for Cognition - Espeso-Gil, Sergio; Holik, Aliaksei Z.; Bonnin, Sarah; Jhanwar, Shalu; Chandrasekaran, Sandhya; Pique-Regi, Roger; Albaigès-Ràfols, Júlia; Maher, Michael; Permanyer, Jon; Irimia, Manuel; Friedländer, Marc R.; Pons-Espinal, Meritxell; et al. (Frontiers in Molecular Neuroscience, 2021)
In early development, the environment triggers mnemonic epigenomic programs resulting in memory and learning experiences to confer cognitive phenotypes into adulthood. To uncover how environmental stimulation impacts the epigenome and genome organization, we used the paradigm of environmental enrichment (EE) in young mice constantly receiving novel stimulation. We profiled epigenome and chromatin architecture in whole cortex and sorted neurons by deep-sequencing techniques. Specifically, we studied chromatin accessibility, gene and protein regulation, and 3D genome conformation, combined with predicted enhancer and chromatin interactions. We identified increased chromatin accessibility, transcription factor binding including CTCF-mediated insulation, differential occupancy of H3K36me3 and H3K79me2, and changes in transcriptional programs required for neuronal development. EE stimuli led to local genome re-organization by inducing increased contacts between chromosomes 7 and 17 (inter-chromosomal). Our findings support the notion that EE-induced learning and memory processes are directly associated with the epigenome and genome organization.